1976
DOI: 10.1073/pnas.73.12.4570
|View full text |Cite
|
Sign up to set email alerts
|

Structure and transformation of chitin synthetase particles (chitosomes) during microfibril synthesis in vitro.

Abstract: The fine structure of isolated chitin synthetase (UDP-2-acetamido-2-deoxy-D-glucose:chitin 4-,B-acetamidodeoxyglucosyltransferase; EC 2.4.1.16) particles (chitosomes) from Mucor rouxii and the elaboration of chitin microfibrils were studied by electron microscopy. Chitosomes are spheroidal, but often polymorphic, structures, mostly 40-70 nm in diameter. Their appearance after negative staining varies. Some reveal internal granular structure enclosed by a shell measuring 6-12 nm thick; others do not show intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
0
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(98 citation statements)
references
References 9 publications
5
92
0
1
Order By: Relevance
“…The presence of such an inactive enzyme has also been demonstrated in 54000g supernatants from cell-free extracts from yeast cells of Mucor rouxii, where it was associated with identifiable particles called chitosomes (Ruiz-Herrera et al, 1975;Bracker et al, 1976). The role of these chitosomes in chitin synthesis has not yet been elucidated but it was suggested that they are extruded through the plasma membrane…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such an inactive enzyme has also been demonstrated in 54000g supernatants from cell-free extracts from yeast cells of Mucor rouxii, where it was associated with identifiable particles called chitosomes (Ruiz-Herrera et al, 1975;Bracker et al, 1976). The role of these chitosomes in chitin synthesis has not yet been elucidated but it was suggested that they are extruded through the plasma membrane…”
Section: Discussionmentioning
confidence: 99%
“…In fungal systems, substantial data have accumulated indicating that chitin synthase activity of at least one chitin synthase isoform (CHS3p) is associated with specialized intracellular microvesicles, known as chitosomes, which exhibit a special lipid and protein composition (Bracker et al, 1976;Hernandez et al, 1981;Florez-Martinez et al, 1990). Electron microscopy has revealed that, in the presence of UDP-GlcNAc and activators, purified chitosomes synthesize microfibrils that crystallize in the lumen of the vesicles (Bracker et al, 1976).…”
Section: Chitin Formationmentioning
confidence: 99%
“…The synthesis of chitin is mediated by membrane-bound chitin synthases (CHSs) that locate to specialized transport vesicles, the chitosomes (Bracker et al, 1976;Leal-Morales et al, 1994;Sietsma et al, 1996) or to the plasma membrane (Duran et al, 1979;Leal-Morales et al, 1988;Martinez and Gozalbo, 1994). The yeast Saccharomyces cerevisiae contains three CHSs that have cell cycle-specific functions in septum formation and during budding (Cabib et al, 2001).…”
Section: Introductionmentioning
confidence: 99%